Endophytic Fungi Isolated from Plants Growing in Central Andean Precordillera of Chile with Antifungal Activity Against Botrytis Cinerea - Cotoras-Tadic, M; Mendoza-Espinola, L; Mendoza-Espinola, L; Parada-Fuentes, R; Vidal-Águila, A (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Botrytis cinerea is an important phytopathogenic fungus affecting the fruit production around the world. This fungus is controlled mainly by using synthetic fungicides, but many resistant isolates have been selected by the indiscriminate use of fungicides. Endophytic fungi or secondary metabolites obtained from them become an alternative method of control for this fungus. The aim of this work was to identify endophytic fungi with antifungal activity against the plant pathogenic fungus B. cinerea isolated from plants from Central Andean Precordillera of Chile. Three endophytic fungi (Ac1, Lc1 and Ec1) with antifungal activity against B. cinerea were isolated from native and endemic plants growing in Central Andean Precordillera of Chile. The isolates Lc1 (isolated from Lithraea caustica) and Ac1 (isolated from Acacia caven) were identified as Alternaria spp. and the isolate Ec1 (isolated from Echinopsis chiloensis) was identified as Aureobasidium spp. The isolated endophytic fungi would inhibit B. cinerea through the secretion of diffusible and volatile compounds affecting the mycelial growth, conidia germination and interestingly, it was also shown that the volatile compounds produced by the three isolated endophytic fungi suppressed the sporulation of B. cinerea. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.